2009
DOI: 10.1007/s10856-009-3836-8
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion, spreading and osteogenic differentiation of mesenchymal stem cells cultured on micropatterned amorphous diamond, titanium, tantalum and chromium coatings on silicon

Abstract: It was hypothesized that human mesenchymal stromal cell (hMSC) can be guided by patterned and plain amorphous diamond (AD), titanium (Ti), tantalum (Ta) and chromium (Cr) coatings, produced on silicon wafer using physical vapour deposition and photolithography. At 7.5 h hMSCs density was 3.0-3.5 x higher (P < 0.0003, except Ti) and cells were smaller (68 vs. 102 microm, P 0.000006-0.02) on patterns than on silicon background. HMSC-covered surface of the background silicon was lower on Ti than AD patterns (P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 36 publications
2
50
0
Order By: Relevance
“…These materials are very stable and have a good biocompatibility [8,9,10] and they are able to resist bacterial adhesion [11]. Tetrahedral amorphous carbon (ta-C) is the form 4 of diamond-like carbon, which is the hardest, strongest, and slickest.…”
mentioning
confidence: 99%
“…These materials are very stable and have a good biocompatibility [8,9,10] and they are able to resist bacterial adhesion [11]. Tetrahedral amorphous carbon (ta-C) is the form 4 of diamond-like carbon, which is the hardest, strongest, and slickest.…”
mentioning
confidence: 99%
“…This is due to the multicomponent nature of adhesion and the way in which surface thermodynamics enables such a multi-component system to be efficiently and sufficiently analysed. When accounting for adhesion it is also usually necessary to consider the wettability characteristics of the material and it has been shown that this factor can aid as a potential prediction mechanism for biological adhesion [1,3,6,42]. From this, the surface free energy of a material, along with the characteristic resulting contact angle evaluated with a liquid, can be directly related to the determination of bioactivity and cell adhesion.…”
Section: The Role Of Wettability In Biological and Microbiological Admentioning
confidence: 99%
“…For instance, taking biological cells as an example, it has been reported that osteoblasts preferentially adhere and proliferate on rough surfaces whilst fibroblasts are known to have an enhanced response on smooth surfaces [25,26]. Leading on from this, mesenchymal stem cells have been reported to have a significant sensitivity to surface roughness and topography [6,27]. It has also been shown that surface chemistry can play a significant role in the manipulation of biological cell growth [52,137,180].…”
Section: Prospectsmentioning
confidence: 99%
See 2 more Smart Citations